Two-factor theory – at the intersection of health care management and patient satisfaction - Bohm J (Dove Medical Press, 2012)
Josef BohmHealth Services Administration, New York City College of Technology, City University of New York, Brooklyn, NY, USAAbstract: Using data obtained from the 2004 Joint Canadian/United States Survey of Health, an analytic model using principles derived from Herzberg’s motivational hygiene theory was developed for evaluating patient satisfaction with health care. The analysis sought to determine whether survey variables associated with consumer satisfaction act as Hertzberg factors and contribute to survey participants' self-reported levels of health care satisfaction. To validate the technique, data from the survey were analyzed using logistic regression methods and then compared with results obtained from the two-factor model. The findings indicate a high degree of correlation between the two methods. The two-factor analytical methodology offers advantages due to its ability to identify whether a factor assumes a motivational or hygienic role and assesses the influence of a factor within select populations. Its ease of use makes this methodology well suited for assessment of multidimensional variables.Keywords: two-factor theory, behavioral theory, sociology of health care, patient satisfaction